Aluminum-Tolerant Pisolithus Ectomycorrhizas Confer Increased Growth, Mineral Nutrition, and Metal Tolerance to Eucalyptus in Acidic Mine Spoil - Louise Egerton-Warburton (Applied and Environmental Soil Science)
Ectomycorrhizal fungi (ECM) may increase the tolerance of their host plants to Al toxicity by immobilizing Al in fungal tissues and/or improving plant mineral nutrition. Although these benefits have been demonstrated in in vitro (pure culture) or short-term nutrient solution (hydroponic) experiments, fewer studies have examined these benefits in the field. This study examined the growth, mineral nutrition, and Al levels in two Eucalyptus species inoculated with three Pisolithus ecotypes that varied in Al tolerance (in vitro) and grown in mine spoil in the greenhouse and field. All three ecotypes of Pisolithus improved Eucalyptus growth and increased host plant tolerance to Al in comparison to noninoculated plants. However, large variations in plant growth and mineral nutrition were detected among the Pisolithus-inoculated plants; these differences were largely explained by the functional properties of the Pisolithus inoculum. Seedlings inoculated with the most Al-tolerant Pisolithus inoculum showed significantly higher levels of N, P, Ca, Mg, and K and lower levels of Al than seedlings inoculated with Al-sensitive ecotypes of Pisolithus. These findings indicate an agreement between the fungal tolerance to Al in vitro and performance in symbiosis, indicating that both ECM-mediated mineral nutrient acquisition and Al accumulation are important in increasing the host plant Al tolerance.